Internal vs External Factors Audit Quality: Which is more Influential in the Period before and during Covid? - Muttaqina, Abida; Dewi, Veni Soraya (Prosiding University Research Colloquium, 2022)
The purpose of this study is to test fee audit, audit tenure, CPA size, audit rotation and audit committee towards audit quality. It is a quantitative study that used secondary data from annual financial report in 2016 up to 2020. The population of this study is food and beverage company listed in BEI in 2016-2020 which was taken using purposive sampling with certain criteria. The method of data analysis is logistic regression. The result of this study shows that fee audit positively affects the quality. However, audit tenure does not affect the quality. A big CPA is believed to has the responsibility to do audit better and more precise because it has more specific connection. Audit rotation also does not affect quality audit. Although, the quantity of KAP doing the audit will not guarantee a quality audit as the result. Committee audit does not affect quality audit. The form of committee audit is just a formality of the regulations owned by POJK.